With or against others? Pay-for-Performance activates aggressive aspects of competitiveness. Issue 5 (3rd September 2022) - Gläser, Daniel; van Gils, Suzanne; Van Quaquebeke, Niels
ABSTRACT: While paying employees for performance (PfP) has been shown to elicit increased motivation by way of competitive processes, the present paper investigates whether the same competitive processes inherent in PfP can also encourage aggressiveness. We tested our hypothesis in three studies that conceptually build on each other: First, in a word completion experiment ( N = 104), we find that PfP triggers the implicit activation of the fighting and defeating facets of competitiveness. Second, in a multi-source field study ( N = 94), co-workers reported more interpersonal deviance from colleagues when the latter received a performance bonus than when they did not. In our final field study ( N = 286), we tested the full model, assessing the effect of PfP and interpersonal deviance mediated by competitiveness: Employees with a bonus self-reported higher interpersonal deviance towards their co-workers, which was mediated by individual competitiveness. These findings underscore that PfP can entail powerful yet widely unstudied collateral effects.